From Couple Therapy 1.0 to a Comprehensive Model: A Roadmap for Sequencing and Integrating Systemic, Psychodynamic, and Behavioral Approaches in Couple Therapy. Issue 3 (13th June 2017) - Nielsen, Arthur C.
Abstract : Couple therapy is a complex undertaking that proceeds best by integrating various schools of thought. Grounded in an in‐depth review of the clinical and research literature, and drawing on the author's 40‐plus years of experience, this paper presents a comprehensive, flexible, and user‐friendly roadmap for conducting couple therapy. It begins by describing "Couple Therapy 1.0, " the basic conjoint couple therapy format in which partners talk to each other with the help of the therapist. After noting the limitations of this model, the paper introduces upgrades derived from systemic, psychodynamic, and behavioral/educational approaches, and shows how to combine and sequence them. The most important upgrade is the early focus on the couple's negative interaction cycle, which causes them pain and impedes their ability to address it. Using a clinical case example, the paper shows how all three approaches can improve couple process as a prerequisite for better problem solving. Additional modules and sequencing choice points are also discussed, including discernment counseling and encouraging positive couple experiences. Abstract : Video Abstract